Addressing Microaggressions in Academic Health: A Workshop for Inclusive Excellence - Kupiri Ackerman-Barger; N. Nicole Jacobs; Regina Orozco; Maya London (Association of American Medical Colleges, 2021)
Introduction Health profession schools have acknowledged the need for a diverse workforce by increasing diversity in recruitment, but little has been done to build inclusive excellence in learning environments. Microaggressions and other forms of mistreatment can increase stress levels and depression and negatively impact academic performance. To increase student performance, retention, and wellness, mitigating microaggressions is needed to promote an inclusive culture. Methods We designed this workshop as a framework to think critically about microaggressions, how they impact the health professions academic environment, and how administrators, faculty, and students can promote inclusion excellence. The workshop included a presentation discussing microaggression theory, seven cases describing microaggressions in the health professions education environment, and discussion and facilitator guides. Cases were based on prior research conducted by the primary author and upon interactions authors shared from their professional experience. Participants completed pre- and postsurveys. Results During six workshops at three different institutions, 138 out of 190 participants (73% response rate), including nursing and medicine faculty, students, and leadership, completed the pre- and postsurveys. Pre- and posttraining measurements found statistically significant improvements in participants' knowledge of the impact of microaggressions, self-efficacy in responding to microaggressions, and commitment to being an active bystander in the face of microaggressions. Participants were highly satisfied with the training. Discussion This humanistic, case-based learning curriculum allows facilitators to guide faculty, student, and leadership conversations to build skills to promote inclusion excellence through preventing microaggressions, repairing and reestablishing relationships, and restoring reputations once microaggressions occur.